PREDIKSI POLA ABRASI DALAM RANGKA MITIGASI BENCANA DI KECAMATAN GEROKGAK, KABUPATEN BULELENG, BALI - I Gst Ngr Yoga Jayantara (Jurnal Sains Informasi Geografi (J SIG), 2022)
Gerokgak Subdistrict has seen a significant change in coastline during the past 20 years, from 1997 to 2017, with the largest change being around 620.6 meters. Of the several factors that cause coastline changes, abrasion is one of the most detrimental factors. Change in coastline caused by abrasion can be categorized as disasters because it is destructive and detrimental, as it threatens ecosystems or buildings behind the coastline. Judging from the tendency of development in Gerokgak District that inclines towards the coast, abrasion could be a devastating disaster for most of the people of Gerokgak Subdistrict. Structures such as PLTU Celukan Bawang, hotels on the beach, temples on the beach, and fish ponds owned by the government and the community will become easy targets for abrasion. Previous research resulted in an analysis of shoreline change from shoreline extraction every five years over a 25-year period. There are 6 coastlines resulting from shoreline extraction in 1995-2020. In this study, the six samples of coastline data that have been obtained will be used to draw a general conclusion on abrasion pattern and then this abrasion pattern will be used to produce extrapolation of the abrasion pattern every five years for the next 10 years, namely 2025 and 2030. This study produced extrapolation calculations for 2025 and 2030 which were achieved using the linear regression method with the aim that a linear coastline pattern could be formed as a consideration for decision making for abrasion disaster mitigation policies that occurred in Gerokgak Subdistrict.